2016
DOI: 10.1016/j.envint.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Association of perfluoroalkyl substances exposure with reproductive hormone levels in adolescents: By sex status

Abstract: Polyfluoroalkyl substances (PFASs) are a group of common chemicals that ubiquitously exist in wildlife and humans. However, few studies have researched the effect of PFASs on reproductive hormones in adolescents. To provide information in this regard, we recruited 225 Taiwanese adolescents aged 13-15years from 2009 to 2010 to investigate the relationship between serum PFASs (PFOS, PFOA, PFBS, PFDA, PFDoA, PFHxA, PFHxS, PFNA and PFTA) and reproductive hormone concentrations using a cross-sectional study design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 49 publications
2
36
8
Order By: Relevance
“…Recently, Zhou and colleagues have reported that higher levels of PFASs are associated with lower testosterone and higher estradiol levels, and these associations seem to be more relevant in males than females. 54 We could speculate that the associations of PFOA and PFNA with increased arterial distensibility could be partly interpreted in light of concomitant alterations in sex hormone levels which, in turn, may influence vascular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhou and colleagues have reported that higher levels of PFASs are associated with lower testosterone and higher estradiol levels, and these associations seem to be more relevant in males than females. 54 We could speculate that the associations of PFOA and PFNA with increased arterial distensibility could be partly interpreted in light of concomitant alterations in sex hormone levels which, in turn, may influence vascular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, girls aged 6–9 years who enrolled in the C8 Health Project also had lower serum T levels with higher exposure to PFOS ( Lopez-Espinosa et al , 2016 ). Although no association was observed for PFOA and PFOS exposures with E2 or T in Chinese adolescent girls, serum T levels decreased by 1.2% (95% CI: −2.2%, −0.1%) with an 1-ng/mL increase in serum PFDoA concentrations ( Zhou et al , 2016 ).…”
Section: Epidemiologic Evidence Linking Pfas Exposure and Ovarian Outmentioning
confidence: 99%
“…Of special interest to this review are mechanisms that may affect the developing organism. Potential mechanisms of action include peroxisome proliferation [ 10 ], mitochondrial dysfunction and oxidative stress [ 11 , 12 ], effects on reproductive hormones including progesterone [HE1] [ 13 , 14 ], estrogen [ 14 ], inhibin [ 13 ], and testosterone [ 15 ], loss of gap junction intercellular communication [ 16 ], and interruption of thyroid function [ 17 ]. In the liver, peroxisome proliferation is much stronger in laboratory rodents than in humans [ 10 ], likely contributing to inter-species cholesterol differences with PFCs including hypolipidemia or decreased cholesterol in mice and hyperlipidemia in humans.…”
Section: Introductionmentioning
confidence: 99%